Непрерывная логика и алгоритмы решения некоторых комбинаторных задач - Левин, В.И. (Кибернетика и системный анализ, 2009)
Сформульовано клас комбінаторних задач, еквівалентних задачі визначення взаємного розміщення n послідовностей інтервалів. Показано, що адекватною математичною моделлю розв’язку поставленої задачі є кінцевий динамічний автомат без пам'яті, а адекватним математичним апаратом — неперервна логіка. Побудовано алгоритми розв’язку. The class of combinatorial problems equivalent to the problem of determination of relative positions of n interval sequences is formulated. It is shown that an adequate mathematical model of solving the stated problem is a finite dynamic automaton without memory and that the adequate mathematical apparatus is continuous logic. Algorithms for the solution of the problem are constructed.